A solution-based temperature sensor using the organic compound CuTsPc - Abdullah, S.M.; Ahmad, Z.; Sulaiman, K. (Molecular Diversity Preservation International, 2014)
An electrochemical cell using an organic compound, copper (II) phthalocyanine-tetrasulfonic acid tetrasodium salt (CuTsPc,) has been fabricated and investigated as a solution-based temperature sensor. The capacitance and resistance of the ITO/CuTsPc solution/ITO chemical cell has been characterized as a function of temperature in the temperature range of 25-80 Â°C. A linear response with minimal hysteresis is observed. The fabricated temperature sensor has shown high consistency and sensitive response towards a specific range of temperature values. Â© 2014 by the authors; licensee MDPI, Basel, Switzerland.